Private vs. Community Management Responses to De-Collectivization: Illustrative Cases from China - Liu, J.; Dong, J.; Long, H.; Xu, T.; Putzel, L. (Ubiquity Press, Ltd., 2020)
Over the last several decades, China has undergone several distinct episodes of collectivization and de-collectivization of forest property rights. China’s latest round of collective forest property reforms, launched in 2003, have promoted individual land holding and management, reviving the longstanding debate on whether privatization would improve profits, rural welfare, and forest management. To uncover reasons for different institutional choices in response to land reform and their effects on forest management, we present two cases, from villages in Guizhou and Yunnan provinces. At the local level, these concepts are confronted by diverse groups of actors and management systems with complex arrangements concerning property and forest use rights. As reforms unfold, they are implemented to differing extents and in various manners, reflecting unique socio-ecological and historical contexts, social relations, community dynamics, and global economic trends. Key factors affecting outcomes were prior traditions, social cohesion, and market incentives to manage resources. In the Guizhou case, with a history of private ownership by people of different social groups and a reliance on restricted timber resources, reforms resulted in a fragmented forest management system. In the Yunnan case, a tradition of collective forest management by a tight-knit social group and access to a lucrative non-timber product resulted in a new and effective collective management system. These findings are important to inform policies on forest property in China and beyond as they call into question a link between privatization and marketization favoring effective resource management.